2016
DOI: 10.15407/microbiolj78.03.099
|View full text |Cite
|
Sign up to set email alerts
|

Trends, Achievements and Prospects of Biotechnology in the Food Industry

Abstract: НАПРЯМИ, ДОСЯГНЕННЯ ТА ПЕРСПЕКТИВИ БІОТЕХНОЛОГІЇ У ХАРЧОВІЙ ПРОМИСЛОВОСТІ У статті проведено аналітичний скринінг можливостей біотехнологіїу харчовій промисловості. Представлено основні напрями застосування біотехнологічних дослідж ень і розробок, охарактеризовано доцільність та актуальність використання генної інженерії, спеціалізованих штамів мікроорганізмів та ферментних препаратів при виробництві харчової продукції з функціональною спрямованістю, високим рівнем якості та безпечності. Сформульовано найважли… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The absence of milk from the alimentation may cause many nutritional disadvantages, such as calcium, phosphorus and vitamin deficiencies, which could be supplemented by consuming fruits and vegetables [45]. Due to the nutrition specifics of vegans, there is a need to use vegetable milk for the ice cream to be manufactured The analysis of scientific and patent information revealed that there are about 35 types of "vegetable milk" today [19], [20]. Such types of milk as rice, soybean, almond, sesame and hempseed milk could be used for vegetarian ice cream [45].…”
Section: Resultsmentioning
confidence: 99%
“…The absence of milk from the alimentation may cause many nutritional disadvantages, such as calcium, phosphorus and vitamin deficiencies, which could be supplemented by consuming fruits and vegetables [45]. Due to the nutrition specifics of vegans, there is a need to use vegetable milk for the ice cream to be manufactured The analysis of scientific and patent information revealed that there are about 35 types of "vegetable milk" today [19], [20]. Such types of milk as rice, soybean, almond, sesame and hempseed milk could be used for vegetarian ice cream [45].…”
Section: Resultsmentioning
confidence: 99%
“…853 (2004), but their residual amounts in food products can cause negative effects on human health [33]. The scientific works [34], [35], [36] described a series of experimental studies, the purpose of which was to determine the residual content of disinfectants and detergents and disinfectants in food products using various methods and techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Modes of milk pasteurization in the production of craft cheese. [9]. The expediency and relevance of using extracts of black cornflower herbal coagulantblack cornflower Centurea spp.…”
Section: Resultsmentioning
confidence: 99%